Do Green Bonds Impact Sustainable Development? An Empirical Analysis - Karaş, Göksel; Celikkol, Hakan (Ekonomika, 2025)
Trying to meet unlimited human needs with limited resources causes production activities to deplete or pollute natural resources. Ensuring the sustainability of natural resources and the environment is essential to leaving a livable world for future generations. The concept of sustainable development, which emerged from this attitude, has been on the agenda of many countries, especially supranational organisations, especially in recent years. Based on this, the present study aims to examine the impact of green bonds issued worldwide on sustainable development with the help of panel data analysis for 17 countries that issued the most GBs in the period of 2014–2022. In the study, fixed effect, random effect and GMM tests were applied. Empirical findings show that GB issuances positively affect the environmental performance, while the development levels of countries have a negative effect. The findings also show that the impact of COVID-19 positively affects environmental performance. In the selected countries, trade openness was not found to affect environmental performance significantly.
Keywords: sustainable development; green bonds; developed countries; panel data analysis